Paraná River hydrometric data from Rosario City, Argentina: 2017 to 2023 - Andrés Antico; Ricardo O Aguiar (PANGAEA, 2024)
We updated the Paraná River hydrometric data available at https://doi.org/10.1594/PANGAEA.882613. Specifically we offer here daily Paraná water levels observed from August 2017 to December 2023 at the staff gauge F described in Antico et al. (2018, https://doi.org/10.1002/2017WR020897; hereafter A18), and provided in the form of Excel spreadsheets by the Argentinian national waterway agency (in Spanish: Dirección Nacional de Control de Puertos y Vías Navegables). We confirmed that all these water level observations passed the quality checks of A18 and we converted them into discharges by using the rating curve of A18. These new updated data capture the 2019 and 2023 floods, and the prolonged discharge drought occurred from 2020 until 2022.